Preparation and Characterization of Lecithin-Nano Ni/Fe for Effective Removal of PCB77. (30th April 2014) - Ding, Shu; Zhao, Lin; Qi, Yun; Lv, Qian-qian
Abstract : A kind of combined material (named lecithin-nano Ni/Fe) that is composed of lecithin and nanoscale Ni/Fe bimetal was synthesized via microemulsion method. The efficacy of such an original material was tested using 3, 3′, 4, 4′-tetrachlorobiphenyl (PCB77) as target pollutant. A microemulsion system was optimized as template to prepare Ni/Fe nanoparticles, which was followed by an insite loading process with the deposition of lecithin carrier. It was proved by the characterization that subtle Ni/Fe nanoparticles can be uniformly dispersed and closely combined with lecithin carrier. Lecithin was an environmentally compatible biosurfactant that acted as both the component of the microemulsion and the functional material to accumulate organic contaminants. It was expected that the combined material can integrate the functions of lecithin and bimetal. The effectiveness was exhibited through the more rapid and sufficient removal of PCB77 by lecithin-nano Ni/Fe than that by blank carrier. Although requiring further improvement, the constitution of lecithin-nano Ni/Fe was a beneficial attempt to acquire the synergistic effect for intensified removal of environmental contaminants. It was promising that the original system and convenient method described in this work will facilitate the development of the organic-inorganic combined materials.